Biophotonic sensor for the detection of creatinine concentration in blood serum based on 1D photonic crystal. Issue 53 (27th August 2020) - Aly, Arafa H.; Mohamed, Doaa; A. Mohaseb, Mona; El-Gawaad, N. S. Abd; Trabelsi, Y.
Abstract : A new biophotonic sensor based on photonic crystal (PC) has been designed for the detection of creatinine concentration in blood, and is considered an important small molecule biomarker of renal dysfunction. Abstract : A new biophotonic sensor based on photonic crystal (PC) has been designed for the detection of creatinine concentration in blood, and is considered an important small molecule biomarker of renal dysfunction. Based on the transfer matrix method (TMM), we theoretically investigated the transmittance spectra of a one dimensional alternating dielectric photonic crystal (PC) designed as (AB) 7 / C /(AB) 7 made of MgF2 (A), CeO2 (B) and creatinine concentration present in blood ( C ). The transmission spectra exhibit resonant peaks within the photonic band gap (PBG) indicative of so-called defect modes, which depend on parameters, such as concentration of creatinine in blood, thickness of defect layer and incident angle. The proposed sensor can determine the physiological levels of creatinine in human blood serum samples. The estimated parameters realize an efficient biophotonic sensor wherein sensitivity was tuned from 136.4 nm per RIU to 306.25 nm per RIU and is very useful for the detection of creatinine.